Observations on Food Consumption Behaviors During the COVID-19 Pandemic in Oman - Ben Hassen, Tarek; El Bilali, Hamid; Allahyari, Mohammad S.; Al Samman, Hazem; Marzban, Soroush (Frontiers in Public Health, 2022)
This paper aims to study the perceptions of the impacts of the COVID-19 pandemic on behaviors related to diet and food shopping on a sample of 356 adults in Oman. The study is based on the results of an Arabic-language online survey conducted between September 15 and October 10, 2020, using the Survey Monkey platform. The questionnaire had 25 questions (multiple options and one option), subdivided into three parts. Respondents were asked to disseminate the survey to their networks as part of the study's snowball sampling method. Descriptive statistics and various statistical tests (e.g., U-Mann Whitney, Kruskal-Wallis, chi-square) have been used to evaluate the study results. The study showed a significant shift in the attitude and behavior of respondents regarding food and health. Indeed, the paper findings indicated (i) a shift to healthier diets, as shown by the fact that 45.5% of the participants increased their intake of fruits and vegetables, 42.4% ate more healthy foods, and 53.1% reduced their intake of unhealthy foods; (ii) an increase in the consumption of local products, owing to food safety concerns, with 25.8% of the cohort stating that they purchase more local food items; (iii) a shift in grocery shopping behaviors, especially with 28.1% of the participants buying more groceries online; (iv) the absence of panic buying in Oman, since 62.36% of the participants said they did not stockpile food items; and (v) a reduction of food waste. Indeed, 78.9% of the participants specified they were not wasting more food than average since the beginning of the pandemic, and 74.72% indicated they were more aware of how much food they were wasting. Surprisingly, COVID-19 appears to bring many beneficial adjustments in Oman to make food consumption more sustainable and healthier.